Enhancing the Potential of Creative Community-Based Tourism of Nakhon Chum Subdistrict, Phitsanulok Province - Jarernpanit, Thannapat; Sangyoka, Suksaman; Chimjan, Orachon (Area Based Development Research Journal, 2021)
The challenges of Nakhon Chum community tourism in Nakhon Thai district of Phitsanulok province are the lack of a variety of activities and the inability to respond to the different tourist behaviors. This study therefore aims to enhance the potential of this community-based tourism. The process consists of 1) community participating in planning and development with researchers; 2) enhancing the creativity in community -based tourism through the development of the tourist information center, the creative tourism route, new tourism activities, as well as community products; and 3) creating online marketing. The result has enhanced the potential of the new generation members of the Nakhon Chum Promoting Community-Based Tourism Club. They become the community communicators in designing the community tourism route and three creative tourism programs with the average travel cost per person. The tourist service center provides information, tourism routes, and activities, including selling the community products such as basketwork, spa salt, and herbal compress ball. Online marketing leads to the value addition and income for the community products. These impacts on the community potential in creative tourism and a variety of tourism activities could match the different tourist behaviors and empower the domestic tourism for the future recovery.